Adenoviral.βARKct Cardiac Gene Therapy Ameliorates Cardiac Function Following Cardiopulmonary Bypass in A Swine Model. Issue 4 (October 2020) - Cong, Mulin; Fan, Yiou; Zhu, Fangfang; Ji, Xianfei; Sun, Liangong; Yang, Ming; Li, Na; Li, Qiao; Tan, Qi
ABSTRACT: Objective: This study is to evaluate the effects of the Adenoviral βARKct (Adv. βARKct) myocardial gene transfection following cardioplegic arrest on cardiopulmonary bypass (CPB) in a swine model. Methods: Swine models of cardioplegic arrest on CPB were established after 5 days of myocardial injection of Adv. βARKct or Adv. luciferase. The pigs were randomized into Adv. βARKct, Control, and Sham groups. Invasive hemodynamics, cardiac function, biomarkers, and tissue morphology were assessed. Results: Baseline data were similar among these groups. Hemodynamics and cardiac function showed a deteriorating trend throughout 6 h after weaning in βARKct and Control groups. Compared with Control group, Adv. βARKct treatment significantly elevated global and regional ventricular function (cardiac output, dp/dtmax, Ejection fraction, peak systolic longitudinal strain, and peak systolic strain rate) and altered hemodynamics (cardiac cycle efficiency and systemic vascular resistance). Moreover, inotropic score in βARKct group was gradually decreased to 5.0 ± 1.1, compared with Control group (6.2 ± 0.9), at 6 h after weaning. Biomarkers in βARKct group were significantly better than in Control group. Meanwhile, βARKct treatment reduced the histopathologic injuries, rescued β1-AR, SERCA2a, and RyR2 levels, and decreased the GRK2 levels in myocardial cells. Conclusion: Adv.βARKct inhibits GRK2 and ameliorates myocardial injuries following cardioplegic arrest on CPB, via stabilizing β1-AR, reducing mitochondrial damages and restoring sarcoplasmic reticulum Ca 2+ -handling protein expression. Abstract : Supplemental Digital Content is available in the text